Predicting osteoporosis preventive behaviors in middle-aged and older urban Shanghai residents: a health belief model-based path analysis in a multi-center population study - Wang, Yichen; Li, Chenrui; Chang, Ruijie; Qiao, Yongxia; Cai, Yong; Shen, Tian (Frontiers in Public Health, 2023)
Background Osteoporosis represents a significant health concern as a widespread metabolic bone condition. In this study, we aim to utilize path analysis to examine the intricate relationships among demographic information, Health Belief Model (HBM) constructs and osteoporosis preventive behavior among Shanghai residents over 40 years of age. Methods A multi-center population study was conducted in 20 volunteer communities in Shanghai, China. Out of the 2,000 participants who volunteered, 1,903 completed the field survey. Results 56.0% of participants were females. Their mean age was 63.64 ± 10.30 years. The self-efficacy score among females (42.27 ± 15.82) was also significantly higher than that among males (40.68 ± 15.20). in the pathway analysis. In the path analysis preventive behaviors were significantly predicted by education (β = 0.082, p < 0.001), knowledge (β = 0.132, p < 0.001) and self-efficacy (β = 0.392, p < 0.001). Conclusions This study highlights the importance of gender, education, knowledge and self-efficacy in promoting OP preventive behaviors using the Health Belief Model. The findings emphasize the need for tailored interventions to address the specific needs of different demographic groups.